Cooperative and Individual Mandala Drawing Have Different Effects on Mindfulness, Spirituality, and Subjective Well-Being - Liu, Chao; Chen, Hao; Liu, Chia-Yi; Lin, Rung-Tai; Chiou, Wen-Ko (Frontiers in Psychology, 2020)
Mandala drawing was first practiced by Tibetan buddhists and then developed by Carl Jung, who believed that mandala drawing has the function of integrating psychological division, enhancing psychological harmony, and preserving personality integrity. Studies on mandala drawing have mainly focused on alleviating people’s negative emotions, such as anxiety and depression, and there exist few empirical studies on the influence of mandala drawing on positive psychology. Therefore, this study explored the effect and mechanism of mandala drawing on the improvement of mindfulness, spirituality, and subjective well-being (SWB) from the perspective of positive psychology as well as the relationship among mindfulness, spirituality, and SWB. A total of 80 students were recruited from Chang Gung University, and the aforementioned three main variables were measured before and after the coloring experiment. The results indicated that SWB increased significantly (mean score of 3.96 and 4.67 at the pre- and post-test, respectively); mindfulness, spirituality, and SWB were positively correlated; and spirituality regulated the relationship between mindfulness and positive emotions. This study highlights the mechanism of mandala drawing and the theoretical understanding of the relationship between mindfulness and SWB. Mandala drawing has a positive effect on SWB, which may provide individuals with a simple and easy method to improve their happiness.